Cover Feature: Smartphone‐based colorimetric chiral recognition of ibuprofen using aptamers‐capped gold nanoparticles. Issue 3 (2nd February 2018) - Ping, Jing; He, Zhenjiang; Liu, Jianshe; Xie, Xuehui
Abstract : DOI:10.1002/elps.201700372 The cover picture shows the application analysis process. Detachment of an enantioselective aptamer from the AuNPs surface and binding with an enantiomer of Ibuprofen lead to AuNPs aggregation, which allows a rapid enantiodiscrimination of Ibuprofen by monitoring the absorbance changes of AuNPs solution. In this case, a discernible red‐to‐purple color change can be observed by naked eye. To characterize the sample's concentration, the app locates the reference colors, and constructs a calibration curve and calculates the shortest distance between target data values and the calibration point. Finally, the analysis results are presented on this screen.